FLUORIDES DEPOSITED DURING POSTERUPTIVE ACTIVITIES ON KAMCHATKAN VOLCANOES - Serafimova E.K. (My University, 1997)
According to their formation conditions, the fluorides are classified in two types - pneumatolytic and metasomatic. They are spatially confined to rootless fumaroles of basalt volcanoes. The main mineral among the fluorides is α-ralstonite. The less common minerals are fluorite, sellaite, malladrite, and elpasolite. The chemical compositions of fluoride-bearing sublimation deposits are presented along with the results of X-ray diffraction and optical analyses. Fluorine mineral assemblages are described.